1217The prevalence of post-traumatic stress disorder in Syrian refugees increased after long-distance migration. (2nd September 2021) - Eiset, Andreas Halgreen; Aoun, Michaelangelo P.; Stougaard, Monica; Gottlieb, Annemarie Graa; Haddad, Ramzi S.; Frydenberg, Morten; Naja, Wadih J.
Abstract: Background: Refugees are forced migrants but there is a large variation in the distance that refugees cover. Previous studies suggest an inverse association between long-distance migration and self-reported health in the general population but there is a knowledge gap in the health effects of migration in refugee populations. Here, we estimate the association between long-distance migration and post-traumatic stress disorder (PTSD), a severe mental health disorder associated with deteriorating mental and somatic health. Methods: Included were 712 adult Syrian refugees and asylum seekers newly arrived in Lebanon and Denmark. PTSD was assessed using the Harvard Trauma Questionnaire, confounding was handled by propensity score-weighting with covariates age, sex, socioeconomic status, trauma experience, and WHO-5-score after multiply imputing missing data, and the 95-percentile confidence interval (CI) was computed by bootstrapping. Results: The prevalence of PTSD was high in both Lebanon (55%) and Denmark (60%). After adjusting for biases the prevalence difference increased to 9 percentage point (95-percentile CI: [-1; 19] percentage point). All sensitivity analysis produced estimates of the same magnitude and direction, except when grossly violating the assumption of multiple imputation which halved the magnitude of the association. Conclusions: Long-distance migration was associated with an estimated 87 additional cases of PTSD for every 1000 Syrian refugees. This is a first step in examining the effects of migration in refugee health. Key messages: Long-distance migration was positively associated with prevalence of post-traumatic stress disorder in Syrian refugees.